Viral encephalitis as a complication of dengue in western Paraná (Research, Society and Development, 2021)
Dengue affected more than 770,000 people in Brazil during the first five months of 2020. Having four different serotypes, it is considered a severe endemic viral infection influenced by urbanization level. Diagnostic confirmation is performed only with the serological IgM and IgG tests, but due to late positivity of these tests, six and nine days respectively, the treatment is almost always empirical. Between 1-5% of dengue cases evolve into neurological disease, both by the immunological reaction, which ends up manifesting itself later in the form of encephalitis. This study reports the case of a patient with post-dengue encephalitis. Initially, the patient AST, 66 years old, sought care complaining of lipothymia and was discharged from hospital after supportive measures. She evolved with dyspeptic symptoms, myalgia and fluctuating level of consciousness, being hospitalized again for treatment. After multidimensional evaluation, computed tomography was performed, which showed no changes. A CSF puncture was also requested. Empirical therapy was performed with Sodium Valproate, Dexamethasone, Ceftriaxone, Panciclovir and supportive treatment for hemodynamic and seizure control. With positive dengue IgG serology, the team maintained therapy for viral encephalitis. The evolution was favorable with minimal sequelae, such as mild proximal weakness and lacunar amnesia. Therefore, it is concluded that infections by dengue virus, as well as by other arboviruses, can cause potentially fatal complications such as viral encephalitis, requiring early diagnosis and intervention.